1999
DOI: 10.1016/s0271-5317(99)00121-9
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of iron/zinc interactions using metal bound to the caseinophosphopeptide 1–25 of β-casein

Abstract: , et al.. Reduction of iron/zinc interactions using metal bound to the caseinophosphopeptide 1-25 of β-casein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…For a molar ration Zn/Fe = 5, zinc inhibits about 50% of the absorption of iron. This rate of inhibition is reduced to 5% when iron has been previously fixed to β(1-25) [14]. The same tendency was obtained in the presence of calcium.…”
Section: Effect Of Other Minerals (Calcium Zinc)supporting
confidence: 74%
See 1 more Smart Citation
“…For a molar ration Zn/Fe = 5, zinc inhibits about 50% of the absorption of iron. This rate of inhibition is reduced to 5% when iron has been previously fixed to β(1-25) [14]. The same tendency was obtained in the presence of calcium.…”
Section: Effect Of Other Minerals (Calcium Zinc)supporting
confidence: 74%
“…At first, the studies in rats have allowed to show the efficiency of β(1-25) on the absorption and bioavailability of iron [10], an efficiency that was confirmed in a first clinical study [11]. Then, the mechanism of absorption of iron associated with the phosphopeptide as well as the effect of the presence of other minerals (zinc) were studied using the perfusion of a ligated rat duodenal loop segment [12][13][14].…”
Section: Phosphopeptides and Bioavailability Of Mineralsmentioning
confidence: 99%
“…As a result, the effects of peptides derived from milk protein hydrolysis during digestion seem to benefit iron solubility rather than zinc solubility when these minerals are jointly present in the same sample – reducing the negative interaction of Zn by the Fe shown in the FbFeZn sample. These results coincide with those published by Pérès et al. (1999), who reported that CPPs, and specifically βCN(1‐25), reduce the negative influence of Zn upon Fe absorption in rats, at different Fe : Zn ratios including 2 : 1, which is very similar to the 2.5 : 1 ratio of the fruit beverages used in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Interaction of iron and CPPs is 100 times stronger than that of other minerals to CPPs (Aït‐oukhatar et al ., ; Ghosh et al ., ), and the obtained complexes of Fe–CPPs seems to be pH‐resistant and partly protected against further hydrolysis while in the digestive tract (Aït‐oukhatar et al ., ; Ani‐Kibangou et al ., ; Boutrou et al ., ). There is some evidence that binding iron to CPPs prevents or reduces the competitive inhibition of iron absorption induced by other divalent minerals (Pérès et al ., ; Miquel & Farré, ). Several studies have been carried out to investigate the nutritional functions of various types of iron–CPP complexes (Aït‐oukhatar et al ., , ; Pérès et al ., ; Bouhallab et al ., ; Chaud et al ., ; Kibangou et al ., ; Gravaghi et al ., ; Miquel & Farré, ; Wang et al ., ), but there are few studies regarding the experimental aspects of generating such compounds.…”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence that binding iron to CPPs prevents or reduces the competitive inhibition of iron absorption induced by other divalent minerals (Pérès et al ., ; Miquel & Farré, ). Several studies have been carried out to investigate the nutritional functions of various types of iron–CPP complexes (Aït‐oukhatar et al ., , ; Pérès et al ., ; Bouhallab et al ., ; Chaud et al ., ; Kibangou et al ., ; Gravaghi et al ., ; Miquel & Farré, ; Wang et al ., ), but there are few studies regarding the experimental aspects of generating such compounds. RSM‐based optimisation of experimental conditions for iron binding to CPPs has not been investigated so far.…”
Section: Introductionmentioning
confidence: 99%